Enhancing resilience: the impact of a near-peer mentoring program on medical students - Pölczman, Lea; Árva, Dorottya; Győrffy, Zsuzsa; Jámbor, Márk; Végh, András; Kristóf, Gergő; Purebl, György; Girasek, Edmond (Frontiers in Education, 2025)
IntroductionEmerging adulthood is a vulnerable period and can be a crisis for many youth, leading to serious mental health problems. Medical students are especially vulnerable due to their high exposure to stressors, requiring enhanced resilience to cope with academic challenges. This study measured the effectiveness of a near-peer mentoring program in terms of resilience.MethodsA non-randomised controlled trial was conducted at Semmelweis University involving 133 medical students. The case group (n = 94) comprised students who participated in a mentoring program as mentors or mentees. The control group (n = 39) did not participate in mentoring. Data was collected at two points, 5 months apart, at the semester’s start (August 2022) and end (February 2023). Self-report measures included sociodemographics, resilience (Connor-Davidson Resilience Scale), and depression (Depression Anxiety and Stress Scale). Statistical analysis involved descriptive statistics and mixed linear models for repeated-measures ANOVA.ResultsResults showed a significant increase in resilience for the case group compared to the control group (F (1, 129) = 5.578, p = 0.020), with no significant main effect of time. There was a significant interaction effect between intervention and time on resilience (F (1.000, 129.000) = 4.915, p = 0.028). Depression scores showed no significant group difference but a significant main effect of time (F (1.000, 129.000) = 4.725, p = 0.032) and the interaction effect between intervention and time on depression (F (1.000, 129.000) = 4.018, p = 0.047).DiscussionThis mentoring program effectively increased resilience and helped maintain mental health, contributing to developing skilled healthcare professionals—where resilience remains a key strength for 21st-century doctors.